Tree microbiome : phyllosphere, endosphere and rhizosphere - Asiegbu, Fred O.; Kovalchuk, Andriy, 1980- (Forest microbiology, 2021)
Forest Microbiology, Volume One: Tree Microbiome: Phyllosphere, Endosphere and Rhizosphere places an emphasis on the microbiology of leaves, needles, stems, roots, litter and soil. This comprehensive title is split into five sections, including the phyllosphere microbiome, endosphere, rhizosphere, archaea, viruses in forest ecosystem and microbiota of forest nurseries and tree pests, challenges and potentials. Microbial communities associated with various host trees and different tree tissues are compared, and generalists and specialists among tree-associated microbes are identified. In addition, biotic and abiotic factors determining the composition and the structure of forest tree microbial communities are presented, along with the concept of microbial 'hubs.' Together, the book's editors have 25 years' worth of experience teaching and conducting research on forest microbiology, making this an essential read for any scientist interested in the forest microbiome.